Alleviation of salinity stress during seed germination in wheat (Triticum aestivum) by potassium applications - YAGMUR, M; KAYDAN, D; OKUT, N (The Indian Journal of Agricultural Sciences, 2011)
A greenhouse pot experiment was conducted during 2004 to study the influence of potassium on 'Tir' wheat (Triticum aestivum, L. emend. Fiori & Paol.) under salt stress. Potassium (K2SO4) was added to soil at 8 levels (0, 100,200, 300,400,500,600,700 mg K/kg dry soil) under salinity stress, and non-salinity condition was used as a control. Soil salinity used in the experiment with salinity concentrations at 8 mmhos/cm. NaCl significantly decreased emergence percentage, dry shoot and root weights, shoot K+:Na+ ratio, Chlorophyll a and b contents and osmotic potential, whereas it increased proline concentrations compared to non-salinity condition in wheat seedlings. The potassium application had positive effects on salinity and alleviated negative effects of salinity on wheat seedling Potassium application significantly increased emergence percentage, dry shoot and root weights, shoot K+:Na+ ratio, chlorophyll a and b contents and osmotic potential, whereas proline concentration decreased in wheat plants under salt stress